2016
DOI: 10.7324/japs.2016.60917
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition and Inhibitory Ability of Methanolic Extract from Pumpkin (Cucurbita pepo L) Seeds on Fe-induced Thiobarbituric acid reactive species in Albino Rat's Testicular Tissue In-Vitro

Abstract: Pumpkin seed has been associated with myriad of medicinal uses in different part of the world. In this study, phenolic composition and Fe 2+ induced thiobarbituric acid reactive species (TBARS) inhibitory ability of methanolic extract from pumpkin seeds in rat's testes homogenates were determined. The extract was prepared with 80% methanol (v/v) and the radicals [(1,1-diphenyl-2 picrylhydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS)] scavenging, Fe 2+ chelation and ferric reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…This finding is in agreement with results provided by others, who demonstrated the inhibitory effect of aqueous extract of Moringa oleifera and Newbuoldia laevis leaves on FeSO4 and Sodium Nitroprusside induced lipid peroxidation in rat testes in vitro [43]. In same study the methanolic extract from the pumpkin seed was shown to modulate FeSO4induced TBARs production in albino rat's testicular tissue in-vitro [44].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with results provided by others, who demonstrated the inhibitory effect of aqueous extract of Moringa oleifera and Newbuoldia laevis leaves on FeSO4 and Sodium Nitroprusside induced lipid peroxidation in rat testes in vitro [43]. In same study the methanolic extract from the pumpkin seed was shown to modulate FeSO4induced TBARs production in albino rat's testicular tissue in-vitro [44].…”
Section: Discussionsupporting
confidence: 92%
“…Although we are still characterizing the bioactive compounds in the methanolic extract, we can speculate that the content of phytochemicals is similar to the C. pepo seed [16]. Some of these components include flavonoids such as quercetin, luteolin, and apigenin, which at low concentration intakes have protective anti-inflammatory effects on human retinal pigment epithelial damage by hypoxia, inhibiting VEGF and factors related to its activation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritionally, pumpkin seed has a high amount of polyunsaturated fatty acids as well as proteins, vitamins, several minerals, and other phytochemicals. The anti-diabetic, antioxidant, anti-carcinogenic, and anti-inflammatory properties of this seed are studied due to its high content of natural bioactive compounds, such as carotenoids, tocopherols, and sterols [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The scavenging ability of the extracts against DPPH (1,1‐diphenyl–2 picrylhydrazyl) radical was evaluated as described by Akomolafe et al (). The method of Oboh, Ademiluyi, et al () was used to determine the ability of the extract to scavenge hydroxyl radical produced from the decomposition of deoxyribose induced by Fe 2+ /H 2 O 2 mixture.…”
Section: Methodsmentioning
confidence: 99%